DEVELOPMENT OF AN ENCYCLOPEDIA OF DAYAK MEDICINAL PLANTS AS A SOURCE FOR LEARNING BIOLOGY ON BIODIVERSITY MATERIALS FOR CLASS X SMA - Yupita Nenet; Hasminar Rachman Fidiastuti; Riantina Fitra Aldya (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
This study aims to develop an encyclopaedia of Dayak medicinal plants in biodiversity material for class X SMA/MA and determine the validity of the products developed. This research is a Research and Development (R&D) study that uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research instruments are in the form of interview sheets, quality assessment questionnaires in the form of checklists using a Likert scale. The assessment was carried out by one material expert, one media expert, one science teacher and 25 grade X students. The results showed that the quality of the encyclopedias developed was in the very valid category according to material experts with a percentage of ideality of 98%; media experts 99% and science teachers 99%. The student response received a very valid category with an idealized percentage of 89.19%. Products that have been developed need to be implemented in order to determine the validity of the product, so that the encyclopedia product can be used as one of the learning resources for class X SMA / MA students.